Atomização e consolidação por fusão seletiva a laser da liga Cu-11,3Al-3,2Ni-3,0Mn-0,5Zr com efeito de memória de forma - Santos, Jonadabe Martins dos (2015)
The aim of the present work was the study of the viability of a manufacturing route of parts with the Cu-based Shape Memory Alloy (SMA) Cu- 11,3Al-3,2Ni-3Mn-0,5Zr through gas atomization followed by Selective Laser Melting (SLM) consolidation. The alloy was prepared from high purity elements in an induction furnace with a concentrate argon flow shield above the molten metal. The atomization was carried out using an induction furnace for melting and argon as atomizer gas. The atomized powder was sieved in 32-106 μm range particles sizes and consolidated by SLM 250 HL device settled at the Leibniz Institute for Solid State and Materials Research, Dresden, Germany. In the consolidation step the best combination of power (P in Watts) and velocity (V in mm/s) were selected through the visual aspect criteria. In the following step the hatching track percentage (S) guided by relative density criteria was included. The atomized powder and the consolidated samples were characterized by optical and electron microscopy, X-ray diffraction and differential scanning calorimetry. The composition and the powder morphology were suitable for the SLM processing. The parameters optimization point out that the best combinations were P310v740S40 and P310v740S50, their relative density were around 97 %. The β’ “zig-zag” martensite phase, the SMA effect cause, was prevailing in the consolidated samples microstructure, still, the microstructure although was not-uniform it was relatively grain refined, pointing out the effect of Zr addition. The consolidated samples transformation temperatures were As=172-174C, Af=194-197C, Ms=156-160C, Mf=132- 138C. The results point to a strong indicative of the viability of a manufacturing route of parts with Cu-based SMA through gas atomization followed by SLM consolidation.